Indonesian Madrasah in the Era of Globalization - R. Dedy Supriatna; Sita Ratnaningsih (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2017)
Abstract This paper aims to review the changing roles of madrasah in Indonesian education, identify challenges and opportunities of madrasah and examine the adaptability of madrasah to global challenges. Historical and sociological approaches were used in order to understand the changing social and political contexts. It is assumed that the main challenges that madrasah is facing is no longer how to internalize Islamic values within the context of nation state, but how prepare young Muslims to play important roles in the globalizing world by pushing role of information technology. In addition, this paper also discuss how the dynamic of global values challenges and influences the well-established Islamic values. The major finding of the study is that while successful in promoting the idea of nation state through its curriculum and school traditions during the New Order Era in Indonesia, madrasah is currently struggling to adapt to the rapidly growing communication technology, implies that Indonesian government supports technology to increase role of madrasah. Abstrak Artikel ini bertujuan untuk mengkaji perubahan peran madrasah dalam pendidikan di Indonesia, mengidentifikasi tantangan dan peluang madrasah dan menguji kemampuan adaptasi madrasah terhadap tantangan global. Pendekatan historis dan sosiologis digunakan untuk memahami konteks sosial dan politik yang berubah. Diasumsikan bahwa tantangan utama yang dihadapi madrasah bukan lagi bagaimana menginternalisasi nilai-nilai Islam dalam konteks negara bangsa, namun bagaimana mempersiapkan pemuda Muslim untuk memainkan peran penting di dunia global dengan mendorong peran teknologi informasi. Selain itu, artikel ini juga membahas bagaimana dinamika nilai-nilai global menantang dan mempengaruhi nilai-nilai Islam yang mapan. Temuan utama dari penelitian ini adalah ketika berhasil mempromosikan gagasan negara dan bangsa melalui kurikulum dan tradisi sekolahnya selama Era Orde Baru di Indonesia, madrasah saat ini berjuang untuk menyesuaikan diri dengan teknologi komunikasi yang berkembang pesat, menyiratkan bahwa pemerintah Indonesia mendukung teknologi untuk meningkatkan peranan madrasah. How to Cite : Supriatna, R. D. Ratnaningsih, S.(2017). Indonesian Madrasah in the Era of Globalization. TARBIYA: Journal of Education in Muslim Society, 4(1), 89-103. doi:10.15408/tjems.v4i1.5908. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.5908